2023
DOI: 10.3390/ijms24098068
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Mechanism and Potential Application of Dental Pulp-Derived Stem Cells in Immune-Mediated Diseases

Abstract: Dental pulp stem cells (DPSCs) are mesenchymal stem cells (MSCs) derived from dental pulp tissue, which have high self-renewal ability and multi-lineage differentiation potential. With the discovery of the immunoregulatory ability of stem cells, DPSCs have attracted much attention because they have similar or even better immunomodulatory effects than MSCs from other sources. DPSCs and their exosomes can exert an immunomodulatory ability by acting on target immune cells to regulate cytokines. DPSCs can also mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 187 publications
0
1
0
Order By: Relevance
“…These findings suggest that macrophages play a pivotal role in the development of pulpal inflammation. Numerous studies have demonstrated that the potent anti-inflammatory and immune-modulating properties of mesenchymal stem cells and their derived exosomes are mainly attributed to their capacity to inhibit T-cell proliferation and the production of cytokines by effector T-cells, such as CD4 + T-helper cells and CD8 + T-cells (Han et al, 2022;Li et al, 2023;Min et al, 2023;Weiss & Dahlke, 2019). One of the most critical immunoregulatory functions of MSCs is their ability to convert conventional T-cells into active and functional regulatory T-cells (Naserian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that macrophages play a pivotal role in the development of pulpal inflammation. Numerous studies have demonstrated that the potent anti-inflammatory and immune-modulating properties of mesenchymal stem cells and their derived exosomes are mainly attributed to their capacity to inhibit T-cell proliferation and the production of cytokines by effector T-cells, such as CD4 + T-helper cells and CD8 + T-cells (Han et al, 2022;Li et al, 2023;Min et al, 2023;Weiss & Dahlke, 2019). One of the most critical immunoregulatory functions of MSCs is their ability to convert conventional T-cells into active and functional regulatory T-cells (Naserian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%